Use of Graphene for Shaped Charge Liner Materials - Tomasz MAJEWSKI; Adam JACKOWSKI (Problemy Mechatroniki)
The paper presents some selected results of tests performed as part of a research task titled "Use of graphene and new multilayer explosive material technologies in shaped charge liner materials". The main aim of the experiments was to test the possibilities of using graphene as an addition to materials used for shaped charge liner production. The primary factors that need to be considered when selecting materials for shaped charge liners are presented. The paper contains a description of the powder materials used, as well as a description of the primary manufacturing steps, encompassing the powder blend preparation, pressing and sintering operations. The results of experiments intended to determine the effects of selected manufacturing process parameters on the porosity of the resulting compacts and sinters are shown, both for products made of pure copper powder and graphene-coated powder. Subsequently, test results for manufacturing of liners made using copper powder pressed using the die and isostatic methods are presented. Liners made of copper powder blends with a varying content of graphene-coated copper powder were also manufactured, and densities and porosities of the resulting sinters were compared.